Visualizing the Beatles : a complete graphic history of the world's favorite band - Pring, John; Thomas, Rob (Dey St., an imprint of William Morrow, 2018)
A visual history of The Beatles illustrates the evolution of their style and sound through infographics that examine the songs on every album, cover designs, chart positions, instruments used, and a wealth of other details.